"A Moment of Science, Please": Activism, Community, and Humor at the March for Science. (October 2021) - Riesch, Hauke; Vrikki, Photini; Stephens, Neil; Lewis, Jamie; Martin, Olwenn
In April 2017, scientists and science sympathizers held marches in the United Kingdom as part of a coordinated international March for Science movement that was held in over 600 cities worldwide. This article reports from participant-observation studies of the marches that took place in London and Cardiff. Supplemented with data from 37 interviews from marchers at the London event, the article reports on an analysis of the placards, focusing on marchers' concerns and the language and images through which they expressed those concerns. How did the protesters articulate their concerns and objectives, and how were these articulations used to build a community? The placards did not represent a clear, focused, and unifying message; they instead illustrated disparate concerns ranging from human-induced climate change, Trump and "alternative facts, " and local UK specific political issues concerning the country's exit from the European Union. Our analysis shows that placards gave a playful and whimsical character to the march, with slogans displaying significant amounts (and moments) of humor, often formulated through insider jokes, scientific puns, or self-deprecating appropriation of negative stereotypes about scientists. We analyze the march through the social movement literature and as a collective identity-building exercise for an (emergent) community of scientists and sympathizers with long-term aims of establishing a louder voice for scientists, and experts, in public discourse.